2006
DOI: 10.1007/s10562-005-9196-1
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of the Sb–V Mixed Oxide on Sb–V–O/SiO2 Catalysts in Methane Selective Oxidation to Formaldehyde

Abstract: Sb-V-O/SiO 2 catalysts were prepared and investigated in methane selective oxidation with O 2 as oxidant. Sb-V-O/SiO 2 catalysts are active and selective in methane selective oxidation. The formaldehyde yield obtained on Sb-V-O/SiO 2 catalysts is clearly higher than that for VO X /SiO 2 and SbO X /SiO 2 catalysts. A one-pass formaldehyde yield up to 3% was obtained on Sb-V-O/SiO 2 catalysts at 650°C. XRD and UV Raman studies showed that the phase of Sb-V mixed oxide on Sb-V-O/SiO 2 catalysts transformed with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Few reports on the effect of the promoter in V-based catalysts on the partial oxidation of methane exist. The Sb-V-O/SiO 2 catalyst was reported to be better than single metal oxide catalysts, such as VO x /SiO 2 and SbO x /SiO 2 , in terms of formaldehyde yield [117]. Formaldehyde yields of up to 3% were achieved at 650 • C with the Sb-V-O/SiO 2 catalyst; moreover, the Sb/V ratio also influences the catalyst performance owing to the phase transformation of the Sb-V mixed oxide [117].…”
Section: Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports on the effect of the promoter in V-based catalysts on the partial oxidation of methane exist. The Sb-V-O/SiO 2 catalyst was reported to be better than single metal oxide catalysts, such as VO x /SiO 2 and SbO x /SiO 2 , in terms of formaldehyde yield [117]. Formaldehyde yields of up to 3% were achieved at 650 • C with the Sb-V-O/SiO 2 catalyst; moreover, the Sb/V ratio also influences the catalyst performance owing to the phase transformation of the Sb-V mixed oxide [117].…”
Section: Promotermentioning
confidence: 99%
“…The Sb-V-O/SiO 2 catalyst was reported to be better than single metal oxide catalysts, such as VO x /SiO 2 and SbO x /SiO 2 , in terms of formaldehyde yield [117]. Formaldehyde yields of up to 3% were achieved at 650 • C with the Sb-V-O/SiO 2 catalyst; moreover, the Sb/V ratio also influences the catalyst performance owing to the phase transformation of the Sb-V mixed oxide [117]. Wallis et al [90] prepared V/Ti-SBA-15 catalysts and found that the Ti promoter contributed to the dispersion and reduction of the VO x species, thereby increasing the activity of the catalyst.…”
Section: Promotermentioning
confidence: 99%
“…Physicochemical properties of inorganic colloidal nanocrystals exhibit high size-and shape-dependences within a scale of 1-10 nm due to quantum confinement effects [1][2][3][4]. A typical example stays within the family of antimony vanadium oxides, including variations of Sb0.92V0.92O4 [5], Sb2V2O9 [6], SbVO4 [7 -10], Sb(VO3)3 [11] and Sb2VO5 [12]. Different from the rutiletype bulk counterpart, its nanocomposite structures strongly depend on their preparatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the rutiletype bulk counterpart, its nanocomposite structures strongly depend on their preparatory conditions. These oxides were found as catalysts for selective oxidation and ammoxidation of methane to formaldehyde [12], and propane to acrylonitrile [13]. In addition, nanoscale antimony vanadium also has potential electrochemical properties in the field of lithium ion batteries [7].…”
Section: Introductionmentioning
confidence: 99%
“…Methanol TPSR profiles show that these materials exhibit highly efficient redox character [14]. They show good performances for the selective oxidation of H 2 S to elemental sulfur [15,16]; for the oxidation of isobutene into methacrolein [17,18]; for the methane selective oxidation to formaldehyde [19]; for the dehydrogenation of alkylbenzenes with carbon dioxide [20][21][22] and for the total oxidation of nitrogen-containing organic volatile compounds [23]. They have also been studied for the propane selective oxidation to acrylic acid [24][25][26][27] and for the propane ammoxidation to acrylonitrile [28,29].…”
Section: Introductionmentioning
confidence: 99%